Pengaruh Citra Merek Dan Promosi Terhadap Keputusan Pembelian Pada Mcdonald’s Cabang Edutown Bumi Serpong Damai - Siti Aprilliani; Andrian Putra Darmawan (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze the influence of Brand Image and Promotion on Purchasing Decisions at McDonald's Edutown Branch, Bumi Serpong Damai. The research method used is quantitative with an associative approach. Data were collected through a questionnaire survey distributed to 100 respondents who are consumers of McDonald's Edutown Branch, Bumi Serpong Damai. The data analysis techniques used are validity testing, reliability testing, classical analysis assumption testing, multiple linear regression, hypothesis testing, and coefficient of determination testing to test the relationship between independent variables (brand image and promotion) to variables (purchase decision) using SPSS version 26. The results of this study are Brand Image influences Purchasing Decisions with the regression equation Y = 18.525 + 0.533 X1, the correlation value is 0.567 meaning that the two variables have a strong relationship. The coefficient of determination value is 0.321 or 32.1% while the rest is influenced by other factors. The hypothesis test obtained thitung > ttabel, namely (6.810 > 1.985), this is also strengthened by p value < sig, 0.05 (0.000 < 0.05). Promotion influences purchasing decisions with the regression equation Y = 13.546 + 0.683 X2, with a correlation value of 0.677, indicating a strong relationship between the two variables. The coefficient of determination is 0.458, or 45.8%, while the remainder is influenced by other factors. The hypothesis test obtained a calculated t value > t table, namely (9.096 > 1.985), which is further supported by a p value < sig. 0.05 (0.000 < 0.05). Brand image and promotion influence purchasing decisions with the regression equation Y = 11.027 + 0.190 X1 + 0.549 X2, with a correlation value of 0.691, indicating a strong relationship between the three variables. The coefficient of determination is 0.478, or 47.8%, while the remainder is influenced by other factors. The hypothesis test obtained a calculated f value > f table, namely (44.380 > 3.09).